Micromagnetic properties of MnAs-on-GaAs(001) films - Ploog, K; Daeweritz, L; Engel-Herbert, R; Hesjedal, T (2006)
Strained MnAs films on GaAs(001) grown by molecular beam epitaxy exhibit unique micro-magnetic properties due to the strain-mediated coexistence of hexagonal ferromagnetic a-MnAs and orthorhombic paramagnetic β-MnAs arranged in selforganized periodic stripe patterns. To explore the internal structure of the magnetization, which is not accessible by the magnetic imaging techniques AFM and XMCDPEEM, detailed micromagnetic simulations are needed. Otherwise, physically unreasonable models would be developed. © 2006 WILEY-VCH Verlag GmbH and Co. KGaA.